The Comparison Between D’Besto and KFC Using Customer Satisfaction & Loyalty - M Ibrahim Shibghaturahman; Deddy Saefuloh (Prosiding Industrial Research Workshop and National Seminar, 2018)
Food is one of the primary needs of every human which absolutely have to be filled. Surely the foods consumed have to be healthy and good for the body. Associated with the business world, many businessman are aware of this need, so that many businessmen have businesses in culinary field, one of which is in fast food segment. So many fast food companies in Indonesia, be it international company like KFC, or local company like D’Besto. In the increasingly fierce competition between national and international companies, each company must be able to provide the best service aside from having good quality products so that customers who consume their products are satisfied with what they buy. The purpose of this study is to measure customer satisfaction and loyalty on fast food companies, especially D’Besto and KFC. The next step is to compare the existing satisfaction and loyalty generated by both party. This research uses 5 variables namely service quality, food quality, perceived value, customer satisfaction, and customer loyalty. And the research method used is descriptive analysis and also regression analysis using SPSS 20 to know the performance of each company. The result is further identified to analyze what needs are to be improved and maintained.